Classwide positive behavior interventions and supports : a guide to proactive classroom management - Simonsen, Brandi; Myers, Diane (Guilford practical intervention in the schools series, 2015)
"A vital classroom management resource, this book shows how to implement positive behavior interventions and supports (PBIS) in K-12 classrooms, regardless of whether PBIS is adopted schoolwide. Practical, step by step guidelines are provided for structuring the classroom environment, actively engaging students in instruction, teaching positive expectations, and establishing a continuum of strategies to reinforce positive behavior and respond to inappropriate behavior. Numerous real world examples and learning exercises are included. In a large size format with lay flat binding for easy photocopying, the book includes reproducible tools for classwide PBIS planning and implementation. Purchasers get access to a Web page where they can download and print the reproducible materials"--Resumé vydavatele